2012
DOI: 10.1021/np300136t
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of β-Carotene Hydroxylase Genes for Astaxanthin Biosynthesis

Abstract: Astaxanthin (3,3'-dihydroxy-4,4'-diketo-β-carotene) (1) is a carotenoid of significant commercial value due to its superior antioxidant potential, application as a component of animal feeds, and ongoing research that links its application to the treatment and prevention of human pathologies. The high commercial cost of 1 is also based upon its complex synthesis. Chemical synthesis has been demonstrated, but produces a mixture of stereoisomers with limited applications. Production from biological sources is lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Professor Basil Weedon's group was the first to prove the structure of astaxanthin by synthesis, in 1975 3 . Astaxanthin, unlike some other carotenoids, is not converted to vitamin A (retinol) in the human body 4 . Too much vitamin A is toxic for a human, animal, but astaxanthin has lower toxicity.…”
Section: Quick Response Codementioning
confidence: 99%
“…Professor Basil Weedon's group was the first to prove the structure of astaxanthin by synthesis, in 1975 3 . Astaxanthin, unlike some other carotenoids, is not converted to vitamin A (retinol) in the human body 4 . Too much vitamin A is toxic for a human, animal, but astaxanthin has lower toxicity.…”
Section: Quick Response Codementioning
confidence: 99%
“…Recent work has suggested that efficient biosynthesis of astaxanthin can proceed from β-carotene to astaxanthin via zeaxanthin. Carotenoid extraction has been studied extensively; for example, the extraction of canthaxanthin (a precursor to astaxanthin) was studied within an E. coli production process and found that extraction efficiency was increased substantially when two solvents, acetone and methanol, were used sequentially rather than as a combined solution (Scaife et al, 2012). Monascus pigments, produced by the fungi Monascus anka and Monascus purpureus, are the best known of the microbial colorants.…”
Section: Production Of Pigmentsmentioning
confidence: 99%
“…Many b-carotene hydroxylase genes have been cloned and characterized, and show immense potential to increase the xanthophyll cycle pool size (Davison et al 2002;Hundle et al 1993;Kim and Keasling 2001;Masamoto et al 1998;Scaife et al 2012;Sun et al 1996). Two b-carotene hydroxylase genes have been cloned and characterized from tomato (Galpaz et al 2006), which locate in different tissues of tomato.…”
Section: Introductionmentioning
confidence: 99%